Building surveys and reports / [electronic resource] - Douglas, James; Noy, Edward A.; Wiley InterScience (Online service) (Oxford : Wiley-Blackwell, 2010)
Deals with structural surveys for all types of building, domestic, industrial & commercial, including diagnoses of a wide range of defects, & a consideration of both modern & older construction methods.
Front Matter -- General Principles and Responsibilities -- Procedure and Equipment -- Measurement of Existing Buildings -- Surveys of Historic Buildings -- Foundation Failures -- Defective Walls and Partitions Above Ground -- Reinforced Concrete, Cladding Materials and Structural Steelwork -- Damp Penetration and Condensation -- Timber Decay and Insect Attack -- Roof Structures and Coverings -- Fireplaces, Flues and Chimney Stacks -- Timber Upper Floors, Floor Coverings, Staircases and Ladders -- Finishes and Joinery Externally and Internally -- Services -- External Works -- Fire and Flood Damage -- Report Writing -- Legal Aspects -- Appendices. Appendix I: Definitions of Inspections and Surveys of Buildings (CIC Explanatory Leaflet) -- Appendix II: Sample Extracts of Survey Schedules & Checklists -- Appendix III: Checklist for Property and Site Surveys -- Appendix IV: Checklist for Building Surveys -- Appendix V: Surveying Safely (Based on RICS 2004) -- Appendix VI: Report on Roof Defects (Village Hall) -- Appendix VII: Report on Property to be Purchased -- Appendix VIII: Glossary of Building Inspection and Related Terms -- Bibliography -- Index.
Previous edition: published as by Edward Noy. 2005.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Building inspection; Buildings -- Defects; Building inspection; Buildings -- Defects; Electronic books